VIII. Congress of Czech and Slovak Pathologists with International Participation - main topic: Interpretation of Immunohistochemical Examinations in Pathology, The; Moravici September 25th-27th, Hradec nad (Biomedical papers, 2001)
VIII. Congress of Czech and SlovakPathologists with InternationalParticipationHradec nad Moravici, September 25th-27th, 2001The main topic: Interpretation of Immunohistochemical Examinations in Pathology
Keywords: Interpretation of Immunohistochemical Examinations in Pathology; VIII. Congress of Czech and Slovak Pathologists with International Participation